Tacuarembemys kusterae, gen. et sp. nov., a new Late Jurassic–?earliest Cretaceous continental turtle from western Gondwana - Perea, Daniel (2014)
A new continental turtle, Tacuarembemys kusterae, gen. et sp. nov., is described on the basis of a partial external mold of the carapace and associated shell bone fragments recovered from the Batoví Member (Late Jurassic–?earliest Cretaceous) of the Tacuarembó Formation, Paraná Basin, Uruguay. The estimated length of the carapace is 18 cm. This new genus and species shows a unique combination of characters: a large nuchal notch, a pair of anterior supernumerary scales, the absence of a cervical scale, and an external surface ornamentation that is macroscopically smooth with some thin linear ridges perpendicular to the margins of the plates and microscopically composed of small, randomly distributed pits. The first two characters resemble those seen in the solemydid Naomichelys speciosa from the Cretaceous of North America, although the ornamentation is markedly different. Although this combination of characters—some shared with other taxa (including cryptodires and pleurodires) and some others that are autapomorphic—allows the recognition of a new genus and species, additional remains are yet needed in order to clarify its phylogenetic relationships. Tacuarembemys kusterae is part of the Priohybodus arambourgi Assemblage Zone, which is of Late Jurassic–?earliest Cretaceous age. This is the first turtle to be discovered in South American continental deposits of that age and thus increases the knowledge on the regional evolution of Mesozoic turtles. The paleoenvironment for this species includes lakes and permanent and ephemeral rivers in arid-to-semiarid climatic conditions.